Hypoxia-induced conversion of sensory Schwann cells into repair cells is regulated by HDAC8 - Nadège Hertzog; Mert Duman; Maëlle Bochud; Valérie Brügger-Verdon; Maren Gerhards; Felicia Schön; Franka Dorndecker; Dies Meijer; Robert Fledrich; Ruth Stassart; Devanarayanan Siva Sankar; Jörn Dengjel; et al. (Nature Communications)
Abstract After a peripheral nerve injury, Schwann cells (SCs), the myelinating glia of the peripheral nervous system, convert into repair cells that foster axonal regrowth, and then remyelinate or re-ensheath regenerated axons, thereby ensuring functional recovery. The efficiency of this mechanism depends however on the time needed for axons to regrow. Here, we show that ablation of histone deacetylase 8 (HDAC8) in SCs accelerates the regrowth of sensory axons and sensory function recovery. We found that HDAC8 is specifically expressed in sensory SCs and regulates the E3 ubiquitin ligase TRAF7, which destabilizes hypoxia-inducible factor 1-alpha (HIF1α) and counteracts the phosphorylation and upregulation of c-Jun, a major inducer of the repair SC phenotype. Our study indicates that this phenotype switch is regulated by different mechanisms in sensory and motor SCs and is accelerated by HDAC8 downregulation, which promotes sensory axon regeneration and sensory function recovery.